Invoice of utility bills reimbursement from BUCG-ABC JV for the period from January 2018 to December 2018 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding utility bills reimbursement from BUCG-ABC JV for the period from January 2018 to December 2018 of BRAC University new campus project.